2014
DOI: 10.1016/j.crvasa.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of children operated for hypoplastic left heart syndrome in Children's Heart Centre

Abstract: c o r e t v a s a 5 6 ( 2 0 1 4 ) e 4 4 9 -e 4 5 5 Children Long-term follow up a b s t r a c t Introduction: Hypoplastic left heart syndrome (HLHS), one of the most serious congenital heart defects, can be surgically paliated using 3 subsequent stages. Long-term results of this approach are reviewed in this study. Methods: Fifty-two consecutive patients (pts.) operated for HLHS from 1999 to 2012 were evaluated retrospectively. Results: Norwood stage I operation was performed at the median age of 6.5 days with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…7 From the Czech Republic, it was reported that 52 patients born 1999-2012 had a survival of 73% including survival after heart transplantation. 11 In a recent national population-based study from New Zealand, Cloete et al reported 56% survival to 1 year of age in hypoplastic left heart syndrome with intention to treat. 12 The improved survival between the early and late birth period was mainly explained by improved survival between stages I and II.…”
Section: Discussionmentioning
confidence: 99%
“…7 From the Czech Republic, it was reported that 52 patients born 1999-2012 had a survival of 73% including survival after heart transplantation. 11 In a recent national population-based study from New Zealand, Cloete et al reported 56% survival to 1 year of age in hypoplastic left heart syndrome with intention to treat. 12 The improved survival between the early and late birth period was mainly explained by improved survival between stages I and II.…”
Section: Discussionmentioning
confidence: 99%
“…mortality that occurs in patients between S1P and S2P) is reported in the literature to be between 11% and 19%. 33 35 Reported mortality rates compare favourably to the literature, with 10 demonstrating lower mortality. 13 16 , 18 , 20 , 27 , 28 , 30 , 31 A 15% mortality was noted by one study, 17 while the remaining studies were <11% when home monitoring was used.…”
Section: Discussionmentioning
confidence: 76%